Middle School Students’ Perception on a Health Promoting School to Prevent Bullying: A Qualitative Study - Masunatul Ubudiyah; Nursalam Nursalam; Tintin Sukartini (Jurnal Ners, 2021)
Introduction: Bullying at school is an old phenomenon in the adolescent group. Despite massive prevention programs, it has not yet resolved by teachers and schools, and this also can affect school climate aspects. The aim of this study was to explore students’ perceptions who are being bullying victims about health promoting schools to prevent bullying at school.Methods: This study used a qualitative case study design. The research sample was 18 middle school students in grades 8 and 9 in East and West Surabaya. A sample was recruited through snowball sampling. Interview guidelines were used to collect the data through in-depth interviews. The data were subjected to thematic analysis.Results: Middle school students identified three   main requirements related to prevent bullying were health education, health services, and healthy school environment. These themes were found among the participants with a bullying victim’s history.Conclusion: Health education, health services, and healthy school environment are the theme for preventing bullying cases at school. To prevent bullying requires collaboration from various parties, such as students, teachers and school policy makers to be able to apply the rules while in school.